Dynamical spectroscopy and microscopy of proteins in cells. (October 2021) - Gruebele, Martin; Pielak, Gary J
Highlights: Cells affect macromolecules with steric and 'quinary' interactions. The crowded cytoplasm is structured on all length scales. Charge-hydrophobe patterning is likely conserved in protein-surface evolution. New spectroscopies enable in-cell studies of the proteome surface in its natural environment. Combining fluorescent-based and NMR-based experiments helps explain protein homeostasis in terms of structure and energetics. Abstract : With a strong understanding of how proteins fold in hand, it is now possible to ask how in-cell environments modulate their folding, binding and function. Studies accessing fast (ns to s) in-cell dynamics have accelerated over the past few years through a combination of in-cell NMR spectroscopy and time-resolved fluorescence microscopies. Here, we discuss this recent work and the emerging picture of protein surfaces as not just hydrophilic coats interfacing the solvent to the protein's core and functional regions, but as critical components in cells controlling protein mobility, function and communication with post-translational modifications.